Assessing the effect of four types of direct mail messages to promote the uptake of residential lead remediation funds - H. Okatch; B. Nkala; J. Beltrami; E. Poy; D. Parmer; J. Nkala; F. Olawole (Elsevier, 2022)
Objective: To examine the efficacy of direct mailing using four types of messaging on promoting the uptake of residential lead remediation (RLR) funds in Lancaster, PA, USA. Study design: We designed a quasi-experiment to assess the effect of 4 RLR messages sent to households in Lancaster, PA by direct mail between September and December 2020: a brief flyer (F); a detailed brochure + the flyer (BF); a health infographic + the flyer (IF); and an application form + the flyer (AFF). Methods: Mailers were sent to addresses in four census tracts; each census tract received a different message. Both English and Spanish versions were sent. The outcomes were the event rate defined as the number of phone call inquiries received, and the number of applications received. The association between type of messaging and household type (owner-vs renter-occupied) was assessed using a chi square test. Results: The event rates for the renter-occupied households were lower than for owner-occupied households, regardless of treatment. The event rates for renter-occupied households in the F, BF, IF and AFF groups were 0.00%, 0.35%, 0.12% and 0.18% respectively compared to 0.93%, 0.45%, 0.86% and 1.32% for homeowners. More applications were received from homeowners, and the event rate of the owner-occupied households was significantly different from that of renter-occupied homes (p-value = 0.001). Conclusions: Event rates and applications received were higher for owner-occupied households than they were for renter-occupied households. Direct mailing of RLR information is feasible especially if households at high risk for lead poisoning are targeted.